Efficacy and safety of photodynamic therapy for non–muscle-invasive bladder cancer: a systematic review and meta-analysis - Li, Haitao; Long, Gongwei; Tian, Jun (Frontiers in Oncology, 2023)
Background Photodynamic therapy (PDT) is a promising treatment for non-muscle-invasive bladder cancer (NMIBC), we conducted this systematic review to comprehensively assess its efficacy and safety. Methods A comprehensive literature research was conducted using PubMed, Web of Science, and Scopus, and studies reporting the safety and efficacy of PDT in NMIBC were included. Complete response (CR) rates, recurrence-free survival (RFS) at different time points, and complication incidences were extracted and synthesized. Pooled results were presented as rates with a 95% confidence interval (95% CI). Results Overall, 28 single arm studies were included in the meta-analysis. For unresectable NMIBC, therapeutic PDT achieved CR in 68% (95% CI: 59%-77%) of patients. Among these CR cases, 71% (95% CI: 56%-85%) and 38% (95% CI: 12%-64%) have a RFS longer than 12 and 24 months, respectively. For Tis patients, the CR rate was 68% (95% CI: 56%-80%), and 84% (95% CI: 48%-100%) and 13% (95% CI: 1%-32%) have a RFS longer than 12 and 24 months. For patients with resectable tumors, post-resection adjuvant PDT could provide a 12 and 24 months RFS in 81% (95% CI:76%-87%) and 56% (95% CI:41%-71%) of them. Especially, for NMIBC patients who failed BCG therapy, adjuvant PDT could still achieve a 1-year and 2-year RFS in 68% (95% CI:51%-86%) and 56% (95% CI:32%-81%) patients. The complications were mostly mild and transient, including lower urinary tract symptoms and photosensitivity. Conclusion Both therapeutic and adjuvant PDT present satisfying safety and efficacy for NMIBC, including these cases that are resistant to the standard of care. As a promising option for NMIBC, PDT deserves further exploration by future high-quality research. Systematic review registration https://inplasy.com/inplasy-2022-11-0043/, INPLASY2022110043.